Engineered nanoplatform mediated gas therapy enhanced ferroptosis for tumor therapy in vivo - Kun Xu; Ke Li; Ye He; Yulan Mao; Xuan Li; Liangshuai Zhang; Meijun Tan; Yulu Yang; Zhong Luo; Peng Liu; Kaiyong Cai (Bioactive Materials)
The high glutathione (GSH) environment poses a significant challenge for inducing ferroptosis in tumor cells, necessitating the development of nanoplatforms that can deplete intracellular GSH. In this study, we developed an engineered nanoplatform (MIL-100@Era/L-Arg-HA) that enhances ferroptosis through gas therapy. First, we confirmed that the Fe element in the nanoplatform undergoes valence changes under the influence of high GSH and H2O2 in tumor cells. Meanwhile, L-Arg generates NO gas in the presence of intracellular H2O2, which reacts with GSH. Additionally, Erastin depletes GSH by inhibiting the cystine/glutamate antiporter system, reducing cystine uptake and impairing GPX4, while also increasing intracellular H2O2 levels by activating NOX4 protein expression. Through these combined GSH-depletion mechanisms, we demonstrated that MIL-100@Era/L-Arg-HA effectively depletes GSH levels, disrupts GPX4 function, and increases intracellular lipid ROS levels in vitro. Furthermore, this nanoplatform significantly inhibited tumor cell growth and extended the survival time of tumor-bearing mice in vivo. This engineered nanoplatform, which enhances ferroptosis through gas therapy, shows significant promise for ferroptosis-based cancer therapy and offers potential strategies for clinical tumor treatment.